Design of magnetic flux detection test system for moving target. Issue 5 (February 2020) - Huang, Kui; Xu, Chaoqun; Liu, Chaobo; Dai, Jialong; Zhang, Shaohua; Yi, Zhong; Meng, Lifei; Xiao, Qi
Abstract: Magnetic detection based on the principle of magnetic flux induction is an important method for moving target detection and tracking. This paper designs and develops a test system based on a magnetic flux detection method in a laboratory environment. The article first introduces the overall design scheme and various components of the test system. Based on the target's magnetic and motion characteristics, a motion simulation test platform is designed and developed. Based on the theoretical derivation and numerical simulation of the magnetic target, a sensor is designed and manufactured. The signal acquisition and analysis equipment acquires and analyzes the induced signals. According to different test purposes, the corresponding test methods are designed and various tests are carried out. The results show that the system design can meet the test requirements of the magnetic flux detection system, which is helpful for further research and optimization of the detection method.